PENANGANAN ANGSURAN TERTUNGGAK DI KOPERASI SYARIAH ARRAHMAH BANJARMASIN DALAM TINJAUAN SOSIOLOGI HUKUM ISLAM - Ryan Rezki Pratama; Muhammad Syarif Hidayatullah (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2021)
This research is motivated by the fact that the Arrahmah Islamic Cooperative as one of the Islamic financial institutions that offers financing products in its business, bears the risk of non performing financing with default actions in the form of installment payments in arrears by members. The research objective in this paper is to examine the sociological review of Islamic law on the handling of installments in arrears that occur in the Arrahmah Islamic Cooperative in Banjarmasin. This type of research is empirical legal research with a sociological approach to Islamic law. The results of the discussion show that in general, the socio-economic factors and the bad character of the members are the factors causing the arrears of installments in Arrahmah Islamic Cooperative. Based on a sociological review of Islamic law, the handling of installments in arrears carried out by the Arrahmah Islamic Cooperative is based on and is influenced by the aspects of the religiosity dimension built, legal handling efforts that refer to Islamic contract law, handling efforts based on the principle of maslahat and justice, and handling efforts based on sympathy and philanthropy.